Stereotaxy in rat models: Current state of the art, proposals to improve targeting accuracy and reporting guideline - De Vloo, Philippe; Nuttin, Bart (Behavioural brain research, 2019)
•We review the literature for subjects, targets, origin and accuracy in rat stereotaxy.•Although 57% of studies referred to it, only 10% of subjects were Paxinos atlas rats.•Most procedures were injections (62%), cannula (20%) and electrode (8%) implantations.•Bregma was origin in 96%, but in 1/3 lambda or interaural point were closer to target.•Implantation accuracy was not checked in 39% and clearly stated in only 8% of studies. Stereotaxy is frequently employed in rodent models for precise brain injections or implantations. We intended to map the current practice in rat stereotaxy and list proposals to improve targeting accuracy. We selected 235 publications on rat stereotaxy from the last 5 years. We collected data on the subjects, targets, coordinate system used, postoperative implant verification and analysis of subjects with off-target implants. Approximately 10,000 rats, mostly Sprague-Dawley and Wistar, were subjected to stereotaxy. Although referenced in 57% of the studies, only 10% of the subjects resembled those used in the Paxinos atlas. Popular procedures were injections (62%) and implantation of cannulas (20%) and electrodes (8%). Right-sided and bilateral targets were more often used than left-sided targets. Bregma served as a stereotaxic origin in 96% of the publications, although for 27% of the targets, the entry was closer to lambda. The Euclidian distance from the target to the interaural line midpoint and to lambda was shorter than to bregma in 38% and 5% of the cases, respectively. Bregma and the dura/brain surface were the most popular dorsoventral References Implantation accuracy was assessed almost exclusively histologically. 39% of the studies did not perform any accuracy check. The number of on-target implants was reported in only 8% of the studies. Only 15% of the publications reported that they excluded subjects with off-target implants. Although well-established, rat stereotaxy could be improved, mainly in acquiring target coordinates, selecting a stereotaxic origin and verifying and reporting accuracy.